Overview of verification tests on AC loss, contact resistance and mechanical properties of ITER conductors with transverse loading up to 30 000 cycles. (13th September 2019) - Yagotintsev, K A; Wessel, W A J; Vostner, A; Devred, A; Bessette, D; Mitchell, N; Nabara, Y; Boutboul, T; Tronza, V; Park, S-H; Yu, W; Martovetsky, N; et al.
Abstract: The ITER magnet system uses cable-in-conduit conductor (CICC) technology with individual strands twisted in several stages resulting in a rope-type cable, which is inserted into a stainless steel conduit. The combination of high current (up to 68 kA) and background magnetic field (up to 13 T) results in large transverse Lorentz forces exerted on the conductors during magnet system operation. The high transverse forces, accompanied with the cyclic nature of the load, have a strong influence on the conductor properties. The Twente Cryogenic Cable Press is used to simulate the effect of the Lorentz forces on a conductor comparable to the ITER magnet operating conditions. An overview is presented of the AC coupling and hysteresis loss, mechanical deformation characteristics and inter-strand contact resistance measurement results obtained on full-size ITER CICCs measured in the Twente Cryogenic Cable Press. The aim of this work is to characterize conductors' electromagnetic and mechanical properties during cycling of the load up to 30 000 cycles. The evolution of the magnetization (AC coupling loss time constant nτ ), mechanical properties and inter-strand resistance R c between selected strands is presented along with loading history. The R c between first triplet strands is also measured as a function of applied load. It is shown that transverse load cycling has a strong influence on the CICC properties. An overview of the results for eight toroidal field conductors, two central solenoid conductors, three poloidal field conductors of different types (PF1&6, PF4, PF5), one main bus-bar and one correction coil conductor is presented.